Crosstalk between Aryl Hydrocarbon Receptor and Glucocorticoid Receptor in Human Retinal Pigment Epithelial Cells - Hong Lan Jin; Yujin Choi; Kwang Won Jeong (International Journal of Endocrinology)
The aryl hydrocarbon receptor (AHR) is known to mediate the cellular reaction involved in processing environmental contaminants and, ultimately, preventing accumulation of unfavorable extra lipids and proteins. Glucocorticoid receptor (GR) mediates the expression of genes associated with anti-inflammatory properties. Because AHR and GR are closely related in lipid metabolic dysregulation and inflammation, we speculate that AHR and GR may play a crucial role in AMD pathogenesis and focus on their crosstalk in human retinal pigment epithelial cells (ARPE-19). However, how AHR and GR regulate each other’s signaling pathways is still poorly understood. In this research, we demonstrate that GR attenuates AHR-mediated gene expression by inhibition of nuclear translocation of AHR mediated by TCDD. Chromatin immunoprecipitation analysis demonstrated that GR repress AHR recruitment and chromatin accessibility response to TCDD + Dex treatment leading to repression of AHR target genes. In contrast, AHR facilitates GR-mediated expression in ARPE-19. AHR increases GR recruitment on GRE of GR target genes. Coimmunoprecipitation assay revealed that AHR is associated with GR in ARPE-19 cells and the interaction is enhanced by the addition of TCDD and Dex. Taken together, these studies provide a molecular mechanism of crosstalk between AHR and GR in target gene expression in ARPE-19 cells.